2022
DOI: 10.1051/0004-6361/202142222
|View full text |Cite
|
Sign up to set email alerts
|

APOGEE-2S view of the globular cluster Patchick 125 (Gran 3)

Abstract: We present detailed elemental abundances, radial velocity, and orbital elements for Patchick 125, a recently discovered metal-poor globular cluster (GC) in the direction of the Galactic bulge. Near-infrared high-resolution (R ∼ 22 500) spectra of two members were obtained during the second phase of the Apache Point Observatory Galactic Evolution Experiment at Las Campanas Observatory as part of the sixteenth Data Release (DR 16) of the Sloan Digital Sky Survey. We investigated elemental abundances for four che… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 71 publications
2
6
0
Order By: Relevance
“…However, they found a more metal-poor cluster with [Fe/H] = −2.37 ± 0.18, relying on the relation between CaT EW and the magnitude of the HB in the Jonhson V filter. On the other hand, our metallicity is in good agreement with that derived by Fernández-Trincado et al (2022) since they obtained a mean [Fe/H] = −1.70, measuring the Fe I lines from the APOGEE-2S data.…”
Section: Patchick 125supporting
confidence: 91%
See 1 more Smart Citation
“…However, they found a more metal-poor cluster with [Fe/H] = −2.37 ± 0.18, relying on the relation between CaT EW and the magnitude of the HB in the Jonhson V filter. On the other hand, our metallicity is in good agreement with that derived by Fernández-Trincado et al (2022) since they obtained a mean [Fe/H] = −1.70, measuring the Fe I lines from the APOGEE-2S data.…”
Section: Patchick 125supporting
confidence: 91%
“…A few examples are VVV-CL001 (Minniti et al 2011;Fernández-Trincado et al 2021a), VVV-CL002, and VVV-CL003 (Moni Bidin et al 2011);FSR 1716 (a.k.a. Minni 22;Minniti et al 2017b); RLGC 1 and 2 (Ryu & Lee 2018); Camargo 1107, 1108, and 1109(Camargo & Minniti 2019; FSR 1758 (Barbá et al 2019;Romero-Colmenares et al 2021); Garro 01 (Garro et al 2020); UKS 1 (Fernández-Trincado et al 2020); Patchick 99 (Garro et al 2021b); FSR 19 and FSR 25 (Obasi et al 2021); VVV-CL160 (Minniti et al 2021a); Minni 48 (Minniti et al 2021b); FSR 1776 (also known as Minni 23; Dias et al 2022); Ton 1 (Fernández-Trincado et al 2021b); and nine other GCs in Garro et al (2022).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the carbon-deficient N-rich field stars, there is a significant population of carbon-deficient aluminum-enriched field stars (hereafter Al-rich stars) that exhibit low and high levels of nitrogen abundance ratios (Fernández-Trincado et al 2020c), suggesting that there are at least two groups of N-rich field stars that have likely been formed from two different nucleosynthetic pathways over a wide range of metallicities. Such anomalous abundance patterns are found in many GCs over a wide range of metallicities (Fernández-Trincado et al 2019d, 2020e, 2021a, 2022aMészáros et al 2020Mészáros et al , 2021Geisler et al 2021;Romero-Colmenares et al 2021;Masseron et al 2019), and even into the most metal-poor MW GC (see e.g., Fernández-Trincado et al 2021e). Thus, the escape of stars from GCs could be a plausible explanation for the presence of these chemically anomalous stars in the Galactic field.…”
Section: Introductionmentioning
confidence: 93%
“…The Gaia mission (e.g. Cantat-Gaudin et al 2019;Castro-Ginard et al 2020) is extremely helpful in that endeavour and has in fact confirmed many of the recently discovered star clusters as GCs, some examples include the following: Garro 01 (Garro et al 2020), FSR 1758 (Barbá et al 2019;Villanova et al 2019;Romero-Colmenares et al 2021), Patchick 99 (Garro et al 2021c), Patchick 125 (Fernández-Trincado et al 2022;Garro et al 2021a, named also Gran 3 by Gran et al 2022), and VVV-GC160 (Minniti et al 2021a;Garro et al 2021d); another nine GCs confirmed by Garro et al (2021d), FSR 19 and FSR 25 (Obasi et al 2021), and Minni48 (Minniti et al 2021c); and another five GCs confirmed in Garro et al (2021a). These studies as well as other ones are fundamental since they can contribute, from a broad point of view, for one to understand the formation and evolution of the MW GC system.…”
Section: Introductionmentioning
confidence: 99%